Home Away from Home - The Role of Social Support for International Students' Adjustment - Lashari, Sana Anwar (Universiti Utara Malaysia Press, 2018)
Purpose - Academic and psychological adjustment of international students is central to their success while pursuing their degrees abroad. However, acculturation stress is abundant and may pose as a challenge. Thus, in this study we examined whether social support mediates the association between acculturation stress and academic and psychological adjustment.